Unusual Extramedullary Plasmacytoma: A Rare but Possible Cause of Lymphadenopathy in Chronic Lymphocytic Leukemia. (7th July 2015) - Chantepie, S. P.; Cabrera, Q.; Mear, J. B.; Salaun, V.; Lechapt-Zalcman, E.; Macro, M.
Abstract : Cervical bilateral lymphadenopathy is a frequent event during chronic lymphocytic leukemia (CLL) natural history. However, lymph node biopsy is generally not required as long as transformation into an aggressive lymphoma (Richter syndrome) is not suspected. We present here a rare case of CLL patient who developed progressive bilateral cervical lymph node and bilateral tonsillar hypertrophy. CLL front-line therapy was ineffective leading to adenectomy and diagnosis of concomitant extramedullary plasmacytoma. Radiotherapy did not result in the disappearance of lymphadenopathy. Adenectomy should be performed in CLL cases to avoid misdiagnosis.